Avaliação físico-química e funcional da algaroba prosopis juliflora proveniente da mesorregião agreste do Rio Grande do Norte - Oliveira, Natalia de Freitas (2011)
Algaroba (Prosopis juliflora) is a typical legume from arid and semi arid regions, which is composed by sugar-rich pods and high protein seeds. Phenolic compounds are secondary metabolites recognized as potent bioactive compounds, found in several vegetables.Therefore, the objective of this work is to characterize the algaroba flour in terms of its physicalchemical composition, total phenolic content, antioxidant activity by DPPH and ABTS methods, a-amylase and a-glycosidase inhibition, as well as to analyze its organic compounds by high performance liquid chromatography (HPLC). Three experimental groups were investigated (seeds, seeds and pod together and only pod), which were prepared by oven drying and posterior grinding. Water and ethanol extracts (70, 80, 100% v/v) were prepared and used for functional studies. Organic compounds were detected by using HPLC equipment coupled to mass spectrometer. Results show important physical-chemical differences among the experimental groups, seeds, seeds and pod together and only pod. The algarroba seed flour is high in protein (49.49%) and fat (3.10%), while the pod flour is especially rich in sugar (60.3% to 67.9%). Algaroba phenolics are concentrated in pod flour, mainly in water extracts (1.30 mg GAEQ/100g sample). All seed extracts showed high DPPH activity and maximum antioxidant activity was registered for ethanol 80% extracts (19.81 μM Trolox/g sample). The ABTS activity ranged from 9.73 to 12.74 μM Trolox/g sample. Nearly all the extracts were able to inhibit α-amylase activity mildly (30.50% to 48.80%), while the maximum α-glycosidase inhibition was observed for pod water extracts (81.03%). Algaroba water extracts proven to be especially rich in organic compounds, observed by the high number of chromatographic peaks. Results demonstrate that algaroba is a potential candidate for further investigations concerning its possible functional applications